ANALISIS FAKTOR YANG MEMPENGARUHI PREFERENSI KONSUMEN PRODUK AIR MINUM DALAM KEMASAN DI BOGOR - Jono M. Munandar, Faqih Udin dan Meivita Amelia (Jurnal Teknologi Industri Pertanian, 2004)
ABSTRACTMineral water is drinkable water with a high mineral salt or gas content, either obtained from a mineral spring or with minerals added.  It is usually sold in bottles and satisfy the minimum standard prevailed.  Nowadays, the need for mineral water increase following the increase of population.  Based on the Central Bureau Statistics (BPS) data, the consumption of mineral water in Indonesia was 1.408.148.000 liter in 1994 and it increased up to 3.643.138.000 liter in 2000. Forestalling the enormous need of fresh and dirt-free water, many corporations are growing to provide and produce mineral water.  A corporation marketer needs to understand what the customer needs, perception, preference and behavior in order to satisfy the customer.  Therefore, analyzing the factors of costumer preference toward the mineral water become important to be investigated.  The purpose of this research is to know the customer characteristics and to identify the attributes of mineral water affecting the customer to choose different type of the products.  The other purpose is to compare some of mineral water brands in the market.  The method used to measure the customer preference is Fishbein Multi Attributes Behavior Model.  Finding shows that the most important attributes to develop mineral water is higiene, followed by smell, price, accessibility, taste, advertisment, packaging and brand images. Generally, costumer prefer the mineral water with brand of Aqua than the other brands.Key words : mineral water,  costumer preferences and Multi Attributes Behavior Model